PERAN KOPERASI TERHADAP PEMBERDAYA EKONOMI RAKYAT DALAM UPAYA PENGEMBANGAN USAHA KECIL DI MASA KRISIS EKONOMI - Sulistyorini, Utami Tri (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2001)
This research is based on assumption that cooperation contribution toward small entrepreneurs’ development has not been felt especially for the coop members. Based on this, the research is aimed at identifying how far cooperation contribution toward small entrepreneurs’ development, also identifying the variety of activies in that cooperation has the biggest contribution. Data is collected through purposive random sampling method. While data is analyzed with ANOVA model. The result of analysis shows that cooperation services and activities have satisfied almost all member and society of cooperation. However, the member and society’s Rural and Urban Cooperation differ in stating the cooperation’s activities, which satisfied them.Based on the cooperation’s activities which can satisfy both member’s and society Rural and Urban Cooperation can be defined the activities which the both cooperation has the biggest contribution. Those are; Capital Loan, Production and Marketing.